Failure of Glial Cell-Line Derived Neurotrophic Factor (GDNF) in Clinical Trials Orchestrated By Reduced NR4A2 (NURR1) Transcription Factor in Parkinson’s Disease. A Systematic Review - Kambey, Piniel Alphayo; Kanwore, Kouminin; Ayanlaja, Abiola Abdulrahman; Nadeem, Iqra; Du, YinZhen; Buberwa, Wokuheleza; Liu, WenYa; Gao, Dianshuai (Frontiers in Aging Neuroscience, 2021)
Parkinson's disease is one of the most common neurodegenerative maladies with unforeseen complex pathologies. While this neurodegenerative disorder's neuropathology is reasonably well known, its etiology remains a mystery, making it challenging to aim therapy. Glial cell-line derived neurotrophic factor remains an auspicious therapeutic molecule for treating Parkinson's disease. Neurotrophic factor derived from glial cell lines is effective in rodents and nonhuman primates, but clinical findings have been equivocal. Laborious exertions have been made over the past few decades to improve and assess GDNF in treating Parkinson's disease (clinical studies). Definitive clinical trials have, however, failed to demonstrate a survival advantage. Consequently, there seemed to be a doubt as to whether GDNF has merit in the potential treatment of Parkinson's disease. The purpose of this cutting edge review is to speculate as to why the clinical trials have failed to meet the primary endpoint. We introduce a hypothesis, "Failure of GDNF in clinical trials succumbed by nuclear receptor-related factor 1 (Nurr1) shortfall". We demonstrate how Nurr1 binds to GDNF to induce dopaminergic neuron synthesis. Due to its undisputable neuro-protection aptitude, we display Nurr1 (also called Nr4a2) as a promising therapeutic target for Parkinson's disease.